2022
DOI: 10.1002/mds.29048
|View full text |Cite
|
Sign up to set email alerts
|

TDP‐43 Proteinopathy Presenting with Typical Symptoms of Parkinson's Disease

Abstract: Accumulation of abnormal transactivation response DNA‐binding protein of 43 kDa (TDP‐43) independently induces dopaminergic neuronal loss in the substantia nigra without Lewy pathology, and results in typical Parkinson's disease‐like motor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, several reports indicated that significant neurodegeneration and cellular dysfunction precede Lewy pathology emerging in the substantia nigra, suggesting these two events may not be pathologically linked[5, 7, 31, 40]. Further, there are emerging data from LRRK2 [30, 35] and other cases [58], that support the presence of clinical PD without synuclein pathology. Further, in support of this concept, subjects with Braak PD stages 1 and 2 exhibit dopaminergic neuronal dysfunction and neuronal loss, even though Lewy body pathology is undetectable in the substantia nigra[5, 40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several reports indicated that significant neurodegeneration and cellular dysfunction precede Lewy pathology emerging in the substantia nigra, suggesting these two events may not be pathologically linked[5, 7, 31, 40]. Further, there are emerging data from LRRK2 [30, 35] and other cases [58], that support the presence of clinical PD without synuclein pathology. Further, in support of this concept, subjects with Braak PD stages 1 and 2 exhibit dopaminergic neuronal dysfunction and neuronal loss, even though Lewy body pathology is undetectable in the substantia nigra[5, 40].…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports indicated that significant neurodegeneration and cellular dysfunction precede Lewy pathology emerging in the substantia nigra, suggesting these two events may not be pathologically linked [5,7,31,40]. Further, there are emerging data from LRRK2 [30,35] and other cases [58], that support the presence of clinical PD without synuclein pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case report described an individual who was thoroughly examined and clinically diagnosed with PD but showed no alpha-synuclein inclusions in any brain region at post-mortem analysis. Rather, phosphorylated TDP-43 protein accumulation was abundant in the SN and in other areas of the brain [83]. These examples suggest that alpha-synuclein accumulation and aggregation may simply be an indicator of cellular dysfunction e.g., autophagic dysregulation, not the culprit that initiates or drives dopaminergic dysfunction in idiopathic PD.…”
Section: Discussionmentioning
confidence: 99%
“…Research continues to find expanding implications of aberrant TDP-43 protein in human diseases. TDP-43 pathology is now known to occur in more than 20 different conditions spanning neurodegenerative, developmental, trauma-related, myopathic, and even neoplastic disease categories [ 2 , 13 , 26 , 27 , 78 , 83 , 129 , 133 , 134 , 157 ]. For example, TDP-43 pathology is often seen in corticobasal degeneration, Perry syndrome, Alexander disease, and the Parkinsonism–dementia complex diseases of Guam and Kii [ 43 , 75 , 148 , 152 , 156 ].…”
Section: Differentiating Late-nc From Other Pathologiesmentioning
confidence: 99%